Novel and rare large deletions in the globin gene clusters causing different types of thalassemia - Coelho, Andreia (2011)
The major component of the red blood cells is hemoglobin A which consists of 2α- and 2β-globin chains encoded by α- and β-globin genes located in two different gene clusters (16p13.3 and 11p.15.5, respectively). Molecular defects (usually point mutation or short deletion) that give rise to a quantitative reduction of the corresponding globin chain, result in a hereditary hypochromic and microcytic anemia called thalassemia. However, rarely, the molecular basis of the pathology could be a large deletion affecting several globin genes and/or their distal regulatory sequence. Four patients with hematological phenotypes suggestive of thalassemia, in whom no globinic molecular abnormalities had been found by standard diagnostic procedures, were screened for deletions in the telomeric region of chromosome 16 and 11, by Multiplex Ligation-dependent Probe Amplification (MLPA) assay. To further characterize the breakpoints of the deletions found, we employed synthetic MLPA probemixes designed in our laboratory, as well as PCR and DNA sequencing. We identified two cases of α-thalassemia caused by two distinct large deletions which remove all α-like structural genes and their distal regulatory sites: both are telomeric, one presents at least 271.14 kb of length and the other, at least, 231 kb. Concerning β-globin cluster screening, two deletions were found: one has at least 186 kb, encloses the entire cluster and its locus control region, and gives rise to a εγδβ0-thalassemia. The other presents at least 3 kb, has its 5’ breakpoint located within the second intron of the β-globin gene and its 3’ end within the L1 repetitive region of the cluster. Both α- and β-cluster larger deletions are novel and were named --CMB/αα and PORTUGUESE εγδβ0-Thal, respectively. The other two smaller deletions, given the uncertainty regarding their breakpoints, might be similar to others already published. In all patients, genotypes are well correlated with the different thalassemic phenotypes presented. MLPA proves to be a useful technique to identify known and unknown large deletions affecting globin gene clusters.